A religiosidade e a espiritualidade dos alunos no curso de formação de psicólogo - Gandelman, Terezinha Carmen (2013)
This thesis aims to understand the religiosity and spirituality of psychology students in their undergraduate training. This is a qualitative research. Initially I reflected on my own experiences spiritual and religious, in order to grasp how it was related to my personal and professional life. Later semidirected conducted interviews with two graduates of the last school year of a psychology course. As a criterion for the selection of respondents considered the time of enrollment in Psychology course, setting the option for students last school year, a period that is supposed to have acquired the knowledge already proposed and performing stages in the clinical area and applying knowledge acquired. Other criteria have been between 20 and 25 years, appreciate the religious and spiritual life and have conditions to express their feelings and thoughts about the subject of the interview. We identified aspects of convergence and divergence in the interviews were grouped into themes that were treated differently: the religious and spiritual beliefs of students of psychology, the world view of respondents and the need to differentiate between religiosity and spirituality; distinction between religiosity and spirituality and the patient's own psychologist, religiosity and spirituality in the practice of clinical psychology, religiousness and spirituality in academic education in psychology. From literature, encompassing religiosity and spirituality, considerations were made and held dialogue with authors from this area on the topics identified for analysis. It is evident that there is need for a thorough look on the inclusion of these topics in the curriculum of the Psychology course as a way to contribute to the personal and professional development of students